PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN STUDI KASUS PADA BANK BRI CABANG BUKITTINGGI - Fitria Fitria (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2017)
This research aims to know the magnitude of the influence of organizational cultureon performance of employees. With respect to the above research purposes then made the hypothesis that the